Kratom induced severe cholestatic liver injury histologically mimicking primary biliary cholangitis: A case report - Gandhi, Darshan (World J Hepatol, 2020)
BACKGROUND: Kratom is a psychoactive substance that is isolated from the plant Mitragyna speciosa. The leaves can be chewed fresh or dried, smoked, or infused similar to herbal teas. The plant leaves have been used by natives of Southeast Asia for centuries. The substance has been used for its stimulant activity at low doses, and as an opium substitute at higher doses due to a morphine like effect. CASE SUMMARY: A 37-year-old female with a history of depression and obesity (body mass index: 32) presented to emergency room with a week-long history of nausea, decreased appetite, fatigue, and two days of jaundice. On admission bilirubin was markedly elevated. Her condition was thought to be due to consumption of Kratom 2 wk before onset of symptoms. Liver biopsy showed changes mimicking primary biliary cholangitis. Patient’s symptoms and jaundice improved quickly. CONCLUSION: The use of Kratom has been on the rise in recent years across the United States and Europe. Several case reports have associated adverse health impact of Kratom-containing products including death due to its ability to alter levels of consciousness. Only a few case reports have highlighted the hepatotoxic effects of Kratom. Even fewer reports exist describing the detailed histopathological changes.